2019
DOI: 10.1017/s1047951119002634
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcome of extracorporeal membrane oxygenation following paediatric cardiac surgery

Abstract: Background:Extracorporeal membrane oxygenation has been widely used after paediatric cardiac surgery due to increasing complex surgical repairs in neonates and infants having complex CHDs.Materials and methods:We reviewed retrospectively the medical records of all patients with CHD requiring corrective or palliative cardiac surgery at King Abdulaziz University Hospital that needed extracorporeal membrane oxygenation support between November 2015 and November 2018.Results:The extracorporeal membrane oxygenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
3
26
1
1
Order By: Relevance
“…In other series, ECMO was a risk factor for operative mortality [21]. In this study, two patients had ECMO, and both of them died [22,23]. Naimo and colleagues [24] found that 32% of DiGeorge syndrome had operative mortality; similarly, in our study, 25% of DiGeorge syndrome had operative mortality.…”
Section: Discussionsupporting
confidence: 72%
“…In other series, ECMO was a risk factor for operative mortality [21]. In this study, two patients had ECMO, and both of them died [22,23]. Naimo and colleagues [24] found that 32% of DiGeorge syndrome had operative mortality; similarly, in our study, 25% of DiGeorge syndrome had operative mortality.…”
Section: Discussionsupporting
confidence: 72%
“…Several reports studied the safety of catheter intervention for patients on ECMO support [7,[17][18][19]. When compared to our study, the results are less promising in our cohort.…”
Section: Cardiac Catheterization For the Patient On Ecmo Supportcontrasting
confidence: 63%
“…Our ECMO protocol and data has been published previously 9 Two patients had ECMO for All three patients survived to hospital discharge. 10 Three patients had postoperative complete heart block, two of them required permanent pacemaker. 11 The postoperative complications are listed in Table 3.…”
Section: Patients Characteristics and Index Operationmentioning
confidence: 97%